The Role of Elderly Posyandu Cadres in Improving Community Welfare - Noer, Rachmawaty M; Agusthia, Mira; Maisyaroh U.P, Septi; Hustadiah, Wiwin (Society : Jurnal Pengabdian Masyarakat, 2025)
One village located in Toapaya District, Bintan Regency, Province of Riau is called South Toapaya Village. With a total area of 90.18 km2, South Toapaya Village is home to approximately 6,000 people. The most common condition mentioned is hypertension. The number of elderly is expected to increase to 1.5 million by 2050. As the number of elderly health problems continue to rise, one of the main issues is hypertension, which is the first illness to appear in elderly. Patients and their families frequently treat hypertension, therefore they continue to use the health facilities when problems arise. This requires cooperation from all parties, including family members and the elderly cadre posyandu. This cadre's presence is necessary for the general public's elderly health. The limited number of cadres in the community will harm health care, especially in Asia. In addition to the benefits of lansia posyandu, the number of kaders must also be taken into consideration so that lansia health communication may be effectively monitored. As of right now, role cadres have been carried out globally. Kader is referred to by the WHO as a community health worker. According to WHO, kader is a group of people who live in a particular region and provide health services to the local population. Even though kader is not a professional health care provider, he has formal education and training so that he can assist health care providers in carrying out specific tasks in the community's daily activities, such as posyandu elderly. As stated, cadre is not a key component in promoting health, but cadres and health workers are important steps in enhancing the general public's health. Elderly cadre is the spearak that is most closely related to elderly. Because cadre that is more frequently sentient to the elderly through posyandu elderly, the role of elderly cadres is very large. In this community service program, the service team focuses on forming new posyandu cadres and providing blood pressure measurement training. This training is expected to help cadres in improving the health of the elderly and knowing about hypertension in general.